Muscle recruitment and stone tool use ergonomics across three million years of Palaeolithic technological transitions. Issue 144 (July 2020) - Key, Alastair J.M.; Farr, Ian; Hunter, Robert; Winter, Samantha L.
Abstract: Ergonomic relationships that minimize muscle activity relative to the creation of cutting stress underpin the design of modern knives, saws, and axes. The Palaeolithic archaeological record, and the > 3 million years of technological behavior that it represents, is predominantly characterized by sharp stone implements used for cutting. To date, we do not know whether Palaeolithic hominins adhered to ergonomic principles when designing stone tools, if lithic technological transitions were linked to ease-of-use advances, or even how muscularly demanding different Palaeolithic tools are on an empirically defined relative basis. Here, we report the results of an experimental program that examines how four key stone tool types, produced between ∼ 3.3 million and ∼ 40 thousand years ago, influence muscle activation in the hominin upper limb. Using standardized laboratory-based tests designed to imitate Pleistocene cutting behaviors, surface electromyography recorded electrical activity (amplitude) in nine muscles across the hand, forearm and shoulder of modern humans during the use of replica Lomekwian, Oldowan, Acheulean and Mousterian stone tools. Results confirm digit flexors and abductors, particularly the first dorsal interosseous and flexor pollicis longus, to be the most heavily recruited muscles during the use of all tool types. Significant differences in muscle activation are, however, identified dependent on the type of stone tool used. Notably, the abductor digiti minimi, flexor pollicis longus, and biceps brachii were highly activated during handaxe use, particularly when compared to the use of Oldowan and Levallois flakes. Results are discussed in light of current understanding on the origin of Lower and Middle Palaeolithic technologies, why specific tool types were produced over others during these periods, and the extent to which early hominins produced ergonomically designed tools.